Equestrian tura: A forgotten traditional game in Anatolia - Turkmen, M. (Nova Science Publishers, Inc., 2023)
The horse, as in the formation of the Turkish steppe nomadic culture, was the main action in the determination, development, and transfer of sports tradition to other cultures. There have been those that are still being done, those on the verge of being forgotten, and those that are forgotten. In this study, the "horse riding tour" in the third class will be examined. The purpose of this study is to record and present it as a written document to at least future generations. Horse tura was played at the village weddings played Afsin. Elbistan, and Goksun of Kahramanmaras. Sariz of Kayseri, Akcadag, and Darende of Malatya, Gurun districts of Sivas. Methot: ace- to-face interviews (live interviews) and document scanning methods were used in the study. Five men and five women were interviewed and the literature was reviewed. The tour game, which was an integral part of social ceremonies in the past; rituals such as invitations, music, awards, and categories were examined under titles. Result: two versions of the game "naked collision" and "liver collision" were found in Kyrgyzstan. It has been determined that the game of horse riding is played in the ceremonies of marriage and circumcision, accompanied by Khidr-nebi, ramming, harvest compilation, spring, and national holidays. It has been found that this game has been played intensively until the 1940s in the city of Elbistan; until the 1970s in Kahramanmaras, Afsin. and Goksun districts, villages on the skirts of Binboga Mountain. © 2023 by Nova Science Publishers, Inc. All rights reserved.